Pregnancy class center application as an alternative effort for antenatal class during the COVID-19 pandemic - Lestari, Ayuning Tias Budi; Runjati, Runjati; Supriyana, Supriyana; Mardiyono, Mardiyono; Sudiyono, Sudiyono (MEDISAINS, 2023)
Background: The outbreak of Coronavirus Disease 2019 (COVID-19) has been designated by WHO as a pandemic, causing health services to be significantly disrupted and delayed globally, especially the implementation of the antenatal class. The participation of pregnant women in antenatal classes in Semarang City is only around 25% of the total number of the public health center in the Semarang city area during the COVID-19 pandemic in 2021. There is need a for media innovation in the antenatal class during the pandemic so that antenatal class can still be carried out safely during the COVID-19 pandemic.Purpose: To produce an antenatal class application that can facilitate pregnant women to attend antenatal classes virtually during the COVID-19 pandemic and test the implementation effect of the application on the knowledge, attitudes, and behavior of pregnant women. Methods: This study uses the Research and Development (R&D) method, divided into five stages (Data Collection, Product Design, Design Validation, Design Revision, and Product Trial).Results: An application has been created named PiCCa (Pregnancy Class Center); the test result is feasible to use with a result of 82% and can be used as antenatal class media with a result of 4.32 (p=0.000). The implementation of the PiCCa application can increase knowledge from 12.8 to 18.13 (p=0.000), attitude from 65.36 to 92.3 (p=0.000), and behavior of pregnant women from 19.53 to 32.2 (p=0.000).Conclusion: The PiCCa application is feasible and can be used as an online media for antenatal classes during the COVID-19 pandemic, and its application has a significant effect on increasing the knowledge, attitudes, and behavior of pregnant women.